2015
DOI: 10.1186/s12868-015-0232-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of peripheral nerve injury on parvalbumin expression in adult rat dorsal root ganglion neurons

Abstract: BackgroundParvalbumin (PV) is a calcium binding protein that identifies a subpopulation of proprioceptive dorsal root ganglion (DRG) neurons. Calcitonin gene-related peptide (CGRP) is also expressed in a high proportion of muscle afferents but its relationship to PV is unclear. Little is known of the phenotypic responses of muscle afferents to nerve injury. Sciatic nerve axotomy or L5 spinal nerve ligation and section (SNL) lesions were used to explore these issues in adult rats using immunocytochemistry.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 79 publications
0
16
0
1
Order By: Relevance
“…The present study also highlights the possibility of promoting nerve regeneration in cellular nerve grafts through SDS-increased NCV, SFI, neurotrophin secretion. NF200 and GAP43 are regeneration-associated markers important in the growth and functional recovery of damaged sensory and motor axons2829, which were also slightly increased by SDS administration.…”
Section: Resultsmentioning
confidence: 99%
“…The present study also highlights the possibility of promoting nerve regeneration in cellular nerve grafts through SDS-increased NCV, SFI, neurotrophin secretion. NF200 and GAP43 are regeneration-associated markers important in the growth and functional recovery of damaged sensory and motor axons2829, which were also slightly increased by SDS administration.…”
Section: Resultsmentioning
confidence: 99%
“…For example, TH and vGLUT3 are primarily expressed in C-LTMRs whereas MRGRPD and MRGPRA3 are found in two separate subgroups of the unmyelinated C nociceptors, parvalbumin in proprioceptors, TrkC in Aδ LTMRs and TrkB in Aβ LTMRs. Several of these markers have also been identified on a functional level by other groups [ 4 , 24 , 48 ]. Moreover, recent study by Patil et al functionally and anatomically corroborated these results and reported additional categorization of DRG sensory neuronal subtypes [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Calbindin (CB) and nitric oxide synthase (NOS) are considered to play a vital role in the induction and transduction of nociception ( Patil et al, 2006 ; Egea et al, 2012 ), whereas transient receptor potential vanilloid 1 (TRVP1) is the receptor for capsaicin, which has been shown to be heat sensitive ( Caterina et al, 1997 ). Calretinin (CR) and parvalbumin (PV) are considered to play a vital role in proprioception ( Ren et al, 1993 ; de Nooij et al, 2013 ; Medici and Shortland, 2015 ), whereas tyrosine hydroxylase (TH) is believed to modulate light-touch sensation ( Brumovsky, 2016 ). These neurochemical markers show species or regional differences in percentage expression and distribution in DRG.…”
Section: Introductionmentioning
confidence: 99%